Television Goes Digital - Gerbarg, Darcy (Springer, 2017)
Television has become a ubiquitous part of our lives, and yet its impact continues to evolve at an extraordinary pace. The evolution of television from analog to digital technology has been underway for more than half a century. Today's digital technology is enabling a myriad of new entertainment possibilities. From jumbotrons in cyberspace to multi-dimensional viewing experiences, digital technology is changing television. Consequently, new advertising metrics that reflect the new viewer habits are emerging. The ability to capture a viewer's interactions changes the advertising proposition. Telephone and wireless companies are challenging the traditional mass media providers—broadcasters, cable and satellite companies—and they’re all finding ways to deliver TV programming, video content and Internet offerings to large and small screens in the home and on the go. This volume showcases insights from industry insiders and researchers from a variety of disciplines. It explores the economic, cultural, technical, and policy implications of digital television, addressing such questions as: How will content be monetized in the future? What programming opportunities become possible with the advent of going digital? Will content still be king or will the conduits gain the upper hand? This book analyzes the digital television evolution: its impacts on the economics of the TV industry, its significance for content creation from Hollywood blockbusters to You Tube, the changing role of the consumer, and what's coming next to a theatre near you.